Group of women. - Unknown:::Creator::::::::::::
Photograph shows eight women in dresses and wearing hats. They are (left-to-right) Mrs. Charles Peiper, Mabel Smith Pelhon, Alice Langford, Ida Robson, Emma Chase, Georgia Winans, Hazel Hopkins (Mrs. Dr. Mark).